EFL Learner Autonomy and Identity through Group Work (The Case of EFL Master One Students at Amar Telidji University, Laghouat ) - BOUALAM , Kaouthar; HACHAN,I Siham (Faculty of Letters and Foreign Languages Department of English, 2016)
The study described in this paper stemmed from the desire to examine the assertion that foreign language learners are more successful when they are allowed to actively participate in their own learning process. This dissertation explores learner autonomy and identity through group work in English as a foreign language from the theoretical lens of constructivism and how may group work enhance learner autonomy and therefore, develop learner identity. Along this study, chapter one presents an overview about learner autonomy and identity While, the second chapter sheds light on learner autonomy through group work inside class and through facebook group out class setting and the effect of group work on learners’ identity construction .To achieve the settled objectives, Chapter three is concerned with data collection and analysis in which research questionnaire as a research instrument has been administrated to EFL master one students at Laghouat University to investigate learners’ perceptions of autonomy .In addition to an online observation that aims at looking closely to the extent to which master students are involved in autonomous learning in facebook group . Results have revealed that group work helps master one students to rely on themselves and develop their autonomous learning.